Gone Dollywood : Dolly Parton's mountain dream - Hoppe, Graham, 1984- (New approaches to Appalachian studies., 2018)
"Dolly Parton isn't just a country music superstar. She has built an empire. At the heart that empire is Dollywood, a 150-acre fantasy land that hosts three million people a year. Parton's prodigious talent and incredible celebrity has allowed her to turn her hometown into one of the most popular tourist destinations in America. The crux of Dollywood's allure is its precisely calibrated Appalachian image, itself drawn from Parton's very real hardscrabble childhood in the mountains of east Tennessee. What does Dollywood have to offer besides entertainment? What do we find if we take this remarkable place seriously? How does it both confirm and subvert outsiders' expectations of Appalachia? What does it tell us about the modern South, and in turn what does that tell us about America at large? How is regional identity molded in service of commerce, and what is the interplay of race, gender, and class when that happens? In Gone Dollywood, Graham Hoppe blends tourism studies, celebrity studies, cultural analysis, folklore, and the acute observations and personal reflections of longform journalism into an unforgettable interrogation of Southern and American identity"--